Persepsi Petani terhadap Budidaya Cabai Sistem Pertanian Terapung di Desa Pelabuhan Dalam, Kecamatan Pemulutan, Ogan Ilir - Hasbi Hasbi; Benyamin Lakitan; Siti Herlinda (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2017)
Hasbi et al, 2017. Farmer Perception to Chilli Cultivtion in Floating Agricultural System in Pelabuhan Dalam Village, Ogan Ilir. JLSO 6(2):126-133.The purpose of this research was to utilize potential waste of local resource especially mineral bottle as a floating raft, to train farmer to construct it, to increase farm production, to socialize how to produce inexpensive, widely available, good quality and environmental friendly floating raft made of mineral bottle, and to evaluate farmers response. This research was conducted at Pelabuhan Dalam Village, Subdistrict of Pemulutan, District of Ogan Ilir. The step of this research were socialization to farmers, display the system of floating cultivation and farmers perception evaluation. The results showed that the system was prospective to be developed based on statements of interested farmers. One of the important finding was that the system was easy to maintenance. The farmers were optimistic that the system could be developed by them selves.